Hadis Ahad Sebagai Sumber Hukum Islam (Pemikiran Imam al-Sarakhsi dan Imam Al-Ghazali, Pendekatan Epistemologi) - Jabbar Sabil; Juliana Juliana (Media Syari'ah, 2017)
Ä¤adÄ«Å aÄ¥Äd is one of the sources of Islamic law. But in practice, the scholars set different conditions as seen in the thoughts of Imam al-SarakhsÄ« and Imam al-GhazÄlÄ«. Therefore, this study examines the nature of Ä¥adÄ«Å aÄ¥Äd according to both Imams, and their views on the criteria for the use of Ä¥adÄ«Å aÄ¥Äd as the source of Islamic law. This research is done by epistemology approach which is part of a study of philosophy science. The technique of completion of research data is done by library research with the method of data analysis, that is a research according to the contents of both Imam. The data analysis is done by the comparative descriptive method that is, to find the relation between thinking with the same thing with equation and difference which is related to Ä¥adÄ«Å aÄ¥Äd as the source of Islamic law. So the author comes to the conclusion of both Imams mentioned that Ä¥adÄ«Å aÄ¥Äd is obliged to be practiced but doesnâ€™t produce knowledge.The opposite side of their opinion is on the terms of practice. Imam al-SarakhsÄ« presupposes the fakih narrator, while Imam al-GhazÄlÄ« doesnâ€™t because according to him the condition of the transmigrants is not realistic and complicates the practice.The analysis of the metaphysical example of Ä¥adÄ«Å aÄ¥Äd fi'liyyah about Ä¥adÄ«Å yellow in the morning prayers indicates that in the Ä¥adÄ«Å the metaphysical condition of the jurists doesnâ€™t increase the probability to certainty, and the absence of the fakih narrator doesnâ€™t diminish its worth. Thus, the practice of Ä¥adÄ«Å aÄ¥Äd is sufficient at the level of probability, so the thought of Imam al-SarakhsÄ« and Imam al-GhazÄlÄ« being complementary is not a contradiction.